STRATEGI PEMASARAN PADA UMKM (STUDI PADA TOKO BUKET RAN FLOW PALU) - Andi Indriani Ibrahim; Muh. Riswandi Palawa; Azzahra Annisa Putri; Ni Luh Sulastri; Ni Gusti Ayu KD Surya Wardani (Ndrumi : Jurnal Ilmu Pendidikan dan Humaniora, 2025)
This study aims to analyze the marketing strategies implemented by the Ran Flow Palu MSME to attract consumer interest and their impact on the sustainability of the business. The study used a descriptive method with a qualitative approach and was conducted at Ran Flow Palu. Data collection techniques included observation, interviews, and documentation with the business owner as the primary informant. The results indicate that Ran Flow Palu implements a marketing strategy through segmentation, targeting, positioning, and the marketing mix (4Ps): product, price, place, and promotion. This strategy has proven effective in building the image of an aesthetic, varied, and affordable bouquet shop, especially for the student and school market segment. Factors such as product quality, more affordable prices, a strategic location, and the use of social media also contribute to the success of this business.